2012
DOI: 10.1017/s0022029912000477
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dry cow antibiotic with and without an internal teat sealant on udder health during the first 100 d of lactation: a field study with matched pairs

Abstract: The objective of this field study was to compare the udder health status as well as the clinical mastitis rate during the first 100 d of lactation in cows that received long-acting dry cow antibiotic alone (group AB) or in combination with an internal teat sealant (group AB + OS). The study was conducted during a 9-month period and included 136 Holstein cows from 12 dairy farms in Hessia, Germany. Between days 1 and 5 after calving a California mastitis test (CMT) was performed. Milk-samples were collected for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
2
9
1
Order By: Relevance
“…Treatment with dry cow intramammary antibiotics and ITS showed a significant reduction in the proportion of S. aureus isolates from 64.0% of CMTpositive quarters at dry-off to 44.0% at post-calving (31.3% cure). This result was in agreement with findings by Mutze et al [11] who reported that there was a reduction of prevalence by 25-75% in the first 100 days of lactation in quarters that received ITS and a long-acting antibiotic. However, our cure rate for S. aureus was low compared to the cure rate of 77% reported in a meta-analysis by Halasa et al [15]; this higher cure rate was for all Staphylococcus species, not just S. aureus.…”
Section: Discussionsupporting
confidence: 93%
“…Treatment with dry cow intramammary antibiotics and ITS showed a significant reduction in the proportion of S. aureus isolates from 64.0% of CMTpositive quarters at dry-off to 44.0% at post-calving (31.3% cure). This result was in agreement with findings by Mutze et al [11] who reported that there was a reduction of prevalence by 25-75% in the first 100 days of lactation in quarters that received ITS and a long-acting antibiotic. However, our cure rate for S. aureus was low compared to the cure rate of 77% reported in a meta-analysis by Halasa et al [15]; this higher cure rate was for all Staphylococcus species, not just S. aureus.…”
Section: Discussionsupporting
confidence: 93%
“…No significant reduction in LS was observed by those same authors between ADCT plus TS and ADCT only groups at their first and third herd tests (P = 0.11 and 0.62, respectively). Mütze et al (2012) showed that the ISCC over the first 3 mo of lactation was not different between ADCT and ADCT + TS treated cows (P = 0.37).…”
Section: Discussionmentioning
confidence: 70%
“…Only a trend toward a reduction in LS was reported by Baillargeon and LeBlanc (2010) at the second herd test, but no treatment effects were found at the first or third herd tests. Mütze et al (2012) found no difference in ISCC between ADCT and ADCT + TS treated cattle over the first 3 mo of lactation. Rabiee and Lean (2013) pooled raw data from Cook et al (2005), Sanford et al (2006), and Baillargeon and LeBlanc (2010), and showed that the estimated LS of cows treated with a combination of ADCT and TS was not significantly different from that of those treated with ADCT only; however, Rabiee and Lean (2013) concluded that further studies were needed in this area.…”
Section: Introductionmentioning
confidence: 69%
“…In the case of BDCT, this was despite the high rate of use (75%), which was similar to that found by Olde Riekerink et al (2010;72%) in a Canadian study. The negative association of BDCT, internal sealants, and not using water in milking preparation with herd SCC is well established (Erskine et al, 1987;Godden et al, 2003;Bhutto et al, 2011;Dufour et al, 2011;Mütze et al, 2012). Some investigators have suggested that the benefits of BDCT, as opposed to selective therapy, Interestingly, the significance of these variables varied depending on the population of respondents.…”
Section: Discussionmentioning
confidence: 90%